Genetic Linear Averaging Algorithm for Zooming Digital Images - Baydaa Bahnam (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, the hypernation of linear averaging algorithm for zooming images is achieved with genetic algorithm. It's applied on a number of samples of images that lack the indistinction of the outline and providing accurate images. The equation of linear averaging is utilized as an objective function in genetic algorithm using several types of crossovers and mutations. A compression among these types is accomplished using two measures (RMSE & PSNR) for evaluating the proposed algorithm. The ratio for zooming is twice as the original images. The accuracy and the efficiency of those images are RMSE = 6.6541 and PSNR = 31.6470 db. A MATLAB 7.10.0(R2010a) environment is used for the programming of proposed algorithm will all applied types of crossovers and mutations.